Microarray data analysis to identify differentially expressed genes and biological pathways associated with Tualang Honey supplementation in NASH animal model - Alias, Mohd Afzal; Abdul Rahim, Roslina; Abdullah, Nor Zamzila; Muhammad, Siti Aeshah @ Naznin; A.Talib, Norlelawati (2021)
Tualang Honey (TH) is a multifloral jungle honey that has been shown to have anti-inflammatory and antioxidant properties. Thus, it has been proposed as a potential supplement in the management of non-alcoholic steatohepatitis (NASH). This study aimed to identify potential key genes and biological process associated with the therapeutic effects of TH in NASH animal model. Twenty Sprague Dawley rats were used in this experiment. Five rats were given standard commercial pellets throughout the experiment and acted as controls. Fifteen rats were subjected to the 12% high-cholesterol diet (HCD) for sixteen weeks to induce NASH. They were then divided into 3 groups, with each group receiving 3 different dosages of TH supplementation for four weeks. RNA was extracted from serum using RNeasy extraction kit (Qiagen) and microarray analysis was performed. A total of 3062 differentially expressed genes (DEGs) were identified including 2788 upregulated genes and 274 downregulated genes in all treated groups. There were 15 genes significantly upregulated including aldehyde dehydrogenase family, cytochrome P450 and nuclear transcription factor. Whilst, 13 genes were significantly downregulated such as apelin, interferon regulatory factor 2 and stearoyl-Coenzyme A. Following pathway enrichment analysis, 34 biological processes were significantly modified (p < 0.05). Among the pathways implicated in the effects of TH were those involved in the inflammatory response, lipid biosynthetic process and cholesterol metabolic process. The present study demonstrated that the DEGs involved in the therapeutic effects of TH were enriched in several pathways and further validation is required to confirm their specific roles.